Another Chapter of the Right Versus Left Story: Is Primary Tumor Location a Prognostic Feature in RAS Mutant Metastatic Colorectal Cancer?. (17th August 2018) - Loupakis, Fotios; Schirripa, Marta; Intini, Rossana; Bergamo, Francesca; Bertorelle, Roberta; Fassan, Matteo; Dadduzio, Vincenzo; Merigliano, Stefano; Pilati, Pierluigi; Urso, Emanuele Luca Damiano; Cillo, Umberto; Rugge, Massimo; et al.
Abstract: Background: The prognostic value of primary tumor location (PTL) in patients with metastatic colorectal cancer (mCRC) was reported by recent analyses in RAS wild‐type patients. Here, we investigated the prognostic value of PTL in RAS mutated mCRC patients. Materials and Methods: PTL was defined as left or right if distal or proximal to the splenic flexure. Primary endpoint was overall survival (OS) according to PTL. Subgroup analyses were conducted according to time to metastases and RAS mutation subtypes. Results: Five hundred sixty‐four patients were included. Left‐ and right‐sided cases were 65% and 35%, respectively. No difference in OS was detected according to PTL (hazard ratio [HR] = 0.99, p = .964). No difference in OS was observed in right versus left when looking at synchronous (HR 0.92, p = .557) or metachronous (HR 1.07, p = .807) patients. Conclusion: No OS difference was detected in RAS mutated mCRC. Molecular and clinical features able to improve prognosis and treatment strategies in this setting are needed. Abstract : Emerging data has led to the identification of right‐sided and left‐sided colorectal cancer (CRC) as two distinct clinical, pathological, and molecular diseases. This article is an analysis of the prognostic impact of primary tumor location in a population of patients with RAS mutated metastatic colorectal cancer.